Attitudes and Participation in Landscaping for the Rreservation of Ancient Sites and the Promotion of Tourism; Case Study: Vientiane District Wall CityWallCity Cluster - SOUVANNAVONG, Viprasith; KHAMMOUNGKHOUN, Anousa; SENGONKEO, Luangphasy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The research study includes two objectives: (1) to study attitudes about the perception, value and preservation of the ancient wall of Vientiane, (2) to study participation in improving the topography and promoting tourism of the Vientiane city wall. The study method is to use quantitative research (Quantitative Research) using a questionnaire with a sample group of 318 people in the area, by analyzing the data to find percentage values ​​and standard deviation values. The results of the analysis show that the attitude towards the perception that Vientiane is an old city surrounded by city walls accounts for 46.86% and enough knowledge about the city wall accounts for 46.54%, the perception that Ku Vieng Road is an old city wall accounts for 57.86%. Attitudes about the traces of the old city walls have a high level of value for the times with a mean value equal ( =3.89, S.D =0.87). In terms of attitudes about preservation and development to improve the scenery, it should be considered according to the reality of actual development, accounting for 75.79%, in terms of activities to promote tourism and serve the community, it is seen that those who choose places to learn history account for 69.81%, those who choose places to meet people account for 56.29%. In terms of attitude regarding the preservation of the old city wall, it is seen that the city wall should be partially built up to see the project of the old city wall, covering 41.82% and in terms of the opinion regarding participation, it is seen in the middle level with an average value ( =2.62, S.D =1.11).